Myogenic Determination and Differentiation of Chicken Bone Marrow-Derived Mesenchymal Stem Cells under Different Inductive Agents - Zhen Zhou; Changbin Zhao; Bolin Cai; Manting Ma; Shaofen Kong; Jing Zhang; Xiquan Zhang; Qinghua Nie (Animals, 2022)
Poultry plays an important role in the meat consumer market and is significant to further understanding the potential mechanism of muscle development in the broiler. Bone marrow-derived mesenchymal stem cells (BM-MSCs) can provide critical insight into muscle development due to their multi-lineage differentiation potential. To our knowledge, chicken BM-MSCs demonstrate limited myogenic differentiation potential under the treatment with dexamethasone (DXMS) and hydrocortisone (HC). 5-azacytidine (5-Aza), a DNA demethylating agent, which has been widely used in the myogenic differentiation of BM-MSCs in other species. There is no previous report that applies 5-Aza to myogenic-induced differentiation of chicken BM-MSCs. In this study, we evaluated the myogenic determination and differentiation effect of BM-MSCs under different inductive agents. BM-MSCs showed better differentiation potential under the 5-Aza-treatment. Transcriptome sequence analysis identified 2402 differentially expressed DEGs including 28 muscle-related genes after 5-Aza-treatment. The DEGs were significantly enriched in Gene Ontology database terms, including in the cell plasma membrane, molecular binding, and cell cycle and differentiation. KEGG pathway analysis revealed that DEGs were enriched in myogenic differentiation-associated pathways containing the PI3K-Akt signaling pathway, the TGF-β signaling pathway, Arrhythmogenic right ventricular cardiomyopathy, dilated cardiomyopathy, and hypertrophic cardiomyopathy, which suggested that BM-MSCs differentiated into a muscle-like phenotype under 5-Aza-treatment. Although BM-MSCs have not formed myotubes in our study, it is worthy of further study. In summary, our study lays the foundation for constructing a myogenic determination and differentiation model in chicken BM-MSCs.